Mrs. smith's spy school for girls eaudiobook - McMullen, Beth (Mrs. Smith's Spy School for Girls, 2019)
A girl discovers her boarding school is actually an elite spy-training program, and she must learn the skills of the trade in order to find her mother in this action-packed middle grade debut. After a botched escape plan from her boarding school, Abigail is stunned to discover the school is actually a cover for an elite spy ring called The Center, along with being training grounds for future spies. Even more shocking? Abigail's mother is a top agent for The Center and she has gone MIA, with valuable information that many people would like to have—at any cost. Along with a former nemesis and charming boy from her grade, Abigail goes through a crash course in Spy Training 101, often with hilarious—and sometimes painful—results. But Abigail realizes she might be a better spy-in-training than she thought—and the answers to her mother's whereabouts are a lot closer than she thinks . . .